Odontogenic atypical trigeminal neuralgia (Эндодонтия Today)
The typical clinical presentation of odontogenic atypical trigeminal neuralgia involves pain in a tooth in the absence of any sign of pathology. The paper is concerned with the problem of the etiology, pathogenesis, clinical picture, principles diagnosis, differential diagnosis and the treatment of odontogenic atypical trigeminal neuralgia. A MEDLINE search was performed for all cases of odontogenic atypical trigeminal neuralgia reported in the literature since 1966. The use of tricyclic antidepressants is most effective among the methods of the treatment.